2017
DOI: 10.1155/2017/4509605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Fragmentation on Productivity in Northwestern Ethiopia

Abstract: Generally, land fragmentation is a universal trait of all agricultural systems which affects farmland productivity and no one had documented a rural society where there was no land fragmentation. Hence, this study sought to ascertain the effects of land fragmentation on farmland productivity in the highland districts of Northwestern Ethiopia by using cross-sectional data collected from 240 respondents during 2015/16 production seasons and analyzed by using linear and Cobb-Douglass production functions. In land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
(31 reference statements)
4
29
0
Order By: Relevance
“…The large family, especially among the agrarian communities, have a number of advantages because it provides a large force for agronomic activities. However, over the period of time larger family size would result in fragmentation of farm land which can have negative consequences over period of time (Alemu et al, 2017). The ndings revealed that most of the respondents in the survey were males.…”
Section: General Household Informationmentioning
confidence: 90%
“…The large family, especially among the agrarian communities, have a number of advantages because it provides a large force for agronomic activities. However, over the period of time larger family size would result in fragmentation of farm land which can have negative consequences over period of time (Alemu et al, 2017). The ndings revealed that most of the respondents in the survey were males.…”
Section: General Household Informationmentioning
confidence: 90%
“…Land consolidation is the integration of several properties and their documents (Alamzadeh, 2015;Aydın et al, 2018) Although land consolidation can be considered the opposite of land fragmentation, this method, especially at large and medium scales, will lead to the re-fragmentation of consolidated land. However, land fragmentation refers to rural areas and the small size, irregular shape, and dispersion of parcels (Alemu et al 2017) and consolidation has been a solution for land fragmentation (Demetriou, 2016). If this broad process is defined, it is a key step in the development process and involves taking land from the owner; land preparation; planning for streets, open spaces and basic services; developed form planning; split the land into building blocks; delivery of the scheduled form (Golland, 2003).…”
Section: Principle Policies and Approachesmentioning
confidence: 99%
“…Land fragmentation (LF) is a universal trait of all agricultural systems that affects farmland productivity, and as yet, no one has documented a rural society where there was no LF [1]. LF is a complex concept that encompasses four aspects: (i) number of plots; (ii) sizes of plots; (iii) shape of plots; and (iv) distances between plots, or distance between plots and homesteads [2][3][4]. Fragmented landholding exerts both positive and negative effects on agricultural performance.…”
Section: Introductionmentioning
confidence: 99%